Proceedings of the Association for Pathology Informatics Bootcamp 2022 - Amrom E. Obstfeld; Victor Brodsky; Alexis B. Carter; Peter Gershkovich; Shannon Haymond; Bruce Levy; John Sinard; Devereaux Sellers; Michelle Stoffel; Ronald Jackups (Elsevier, 2023)
The Pathology Informatics Bootcamp, held annually at the Pathology Informatics Summit, provides pathology trainees with essential knowledge in the rapidly evolving field of Pathology Informatics. With a focus on data analytics, data science, and data management in 2022, the bootcamp addressed the growing importance of data analysis in pathology and laboratory medicine practice. The expansion of data-related subjects in Pathology Informatics Essentials for Residents (PIER) and the Clinical Informatics fellowship examinations highlights the increasing significance of these skills in pathology practice in particular and medicine in general. The curriculum included lectures on databases, programming, analytics, machine learning basics, and specialized topics like anatomic pathology data analysis and dashboarding.